Amino- and thiol-modified microporous silicalite-1 and mesoporous MCM-48 materials as potential effective adsorbents for Pb(II) in polluted aquatic systems - Abeer A Malhis; Sharif H Arar; Manar K Fayyad; Hamdallah A Hodali (Adsorption Science & Technology)
Aluminum-free zeolite silicalite-1 and the ordered mesoporous silicates Mobile Crystalline Material No. 48 (MCM-48) were prepared and functionalized with 3-aminopropyltriethoxysilane (APTES) and 3-mercaptopropyltrimethoxysilane (MPTMS) for the enhancement of adsorption capacity. Functionalization via post synthesis grafting method was adopted and the functionalized silicate systems were denoted as silicalite-1-NH 2 , silcalite-1-SH, MCM-48-NH 2 and MCM-48-SH. Functionalization, that was confirmed by XRD, FT-IR and surface area measurements, indicated no structural changes on the silicate materials. The adsorption of Pb(II) ions into these modified silicates was investigated in aqueous solutions with optimized pH at 5.5 where adsorption influencing factors including contact time, adsorbent dose and metal ion initial concentration were studied. Adsorption experimental data for silicalite-1-NH 2 , MCM-48-NH 2 and MCM-48-SH showed satisfactory correlation with Langmuir and Freundlich models. According to Langmuir isotherm, the maximum capacities for the above three modified silicate systems, for 100 ppm Pb(II) dose, are 43.5, 75.2 and 31.2 mg/g and with K f constant values of 16.9, 44.4 and 12.0 L/mg from Freundlich isotherm, respectively. The three modified silicate systems exhibited complete sequestration of Pb(II) ion concentrations in the range 0.48–1.7 ppm from samples collected from Zarqa River in four seasons of the year 2013.